Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Keetsahnak: our missing and murdered Indigenous sisters - Anderson, Kim; Campbell, Maria; Belcourt, Christi (The University of Alberta Press, 2018)
«In Keetsahnak / Our Murdered and Missing Indigenous Sisters, the tension between personal, political, and public action is brought home starkly. This important collective volume both witnesses the significance of the travelling exhibition Walking With Our Sisters and creates a model for antiviolence work from an Indigenous perspective. The contributors look at the roots of violence and how it diminishes life for all. They acknowledge the destruction wrought by colonial violence, and also look at controversial topics such as lateral violence, challenges in working with "tradition," and problematic notions involved in "helping." Through stories of resilience, resistance, and activism, the editors give voice to powerful personal testimony and allow for the creation of knowledge.»-- Provided by publisher.
Keywords: activisme; amériques; anti-violence; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; féminicide; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; régions géographiques; résistance; système colonial; systèmes d'oppressions; thématiques; violences

Le racisme est un problème de blancs - Eddo-Lodge, Reni; Mazoyer, Renaud (Éditions Autrement, 2018)
« Quand des Blancs feuillettent un magazine, surfent sur Internet ou zappent à la télévision, il ne leur semble jamais étrange de voir des gens qui leur ressemblent en position d'autorité. Les affirmations positives de la blanchité sont tellement répandues que le Blanc moyen ne les remarque même pas. Etre blanc, c'est être humain ; être blanc, c'est universel. Je ne le sais que trop, car je ne suis pas blanche." Après l'élection de Barack Obama, certains ont proclamé l'avènement d'une société post-raciale. Avec une liberté de ton décapante, Reni Eddo-Lodge montre ici combien nous en sommes loin. Elle analyse les méfaits d'un racisme structurel persistant d'autant plus sournois qu'il avance masqué. Car le racisme va bien au-delà de la discrimination ou de l'injure personnelle. Il imprègne le récit historique, l'imaginaire collectif, les institutions et les entreprises. Pourquoi les Blancs pensent-ils ne pas avoir d'identité raciale? Pourquoi la simple idée d'un James Bond noir fait-elle scandale? Comment une fillette noire en vient-elle à se persuader qu'en grandissant, elle deviendra blanche? Le racisme n'est pas une question de valeur morale, mais d'exercice du pouvoir. Entretenir la légende d'une égalité universelle n'aide en rien. Au contraire. Car, pour déconstruire le racisme, il faut commencer par reconnaître l'étendue du privilège blanc. »-- 4ème de couverture.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afro-féminisme; approches et analyses; com5170; communication; cours; discipline; europe; féminisme afropéen; histoire et politique; journalisme; premier cycle; privilèges; périodes historiques; racisme; racisme systémique; représentation des femmes* racisées; royaume-uni; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Whose Land Is It Anyway?: a Manual for Decolonization - McFarlane, Peter; Schabus, Nicole (Federation of Post-Secondary Educators of BC, 2018)
We are pleased to announce the publication of Whose Land Is It Anyway? A Manual for Decolonization; inspired by a 2016 speaking tour by Arthur Manuel, less than a year before his untimely passing in January 2017. The book contains two essays from Manuel, described as the Nelson Mandela of Canada, and essays from renowned Indigenous writers Taiaiake Alfred, Glen Coulthard, Russell Diabo, Beverly Jacobs, Melina Laboucan-Massimo, Kanahus Manuel, Jeffrey McNeil-Seymour, Pamela Palmater, Shiri Pasternak, Nicole Schabus, Senator Murray Sinclair, and Sharon Venne. FPSE is honoured to support this publication.
Keywords: amériques; approches et analyses; canada; cours; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Danser sur le dos de notre tortue = Niimtoowaad mikinaag gijiying bakonaan: nouvelle émergence des Nishnaabeg - Simpson, Leanne Betasamosake; Régimbald, Anne-Marie (Collection Proses de combat, 2018)
"On parle beaucoup au Québec, comme dans le reste du Canada, de réconciliation avec les Premières Nations. Mais pour qu'un rapprochement fécond puisse avoir lieu, qu'une nouvelle ère, égalitaire et respectueuse, s'ouvre, le cadre constitutionnel canadien ne peut à lui seul en définir les règles. Toute entente devra aussi tenir compte des traditions autochtones. C'est dans ce contexte que le livre de Leanne Simpson trouve toute sa pertinence. L'auteure s'y demande comment redonner force, consistance et valeur à un héritage politique, juridique et culturel mis à mal par le processus colonial. D'une façon aussi concrète que tonique et audacieuse, elle y explore la langue, les mythes, les coutumes et les expériences de sa culture ancestrale afin de recouvrer et révéler cette manière singulière et originale d'être au monde trop longtemps méprisée. Si l'entreprise est inspirante pour toute communauté issue des Premières Nations, elle l'est également pour quiconque s'intéresse aux contradictions de la modernité occidentale."-- Renaud-Bray.
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; féminisme autochtone; histoire et politique; lit3495; militance; ojibwa; premier cycle; premières nations; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences; études littéraires